Systematic Review into Diagnostics for Post-Kala-Azar Dermal Leishmaniasis (PKDL) - Emily R. Adams; Inge Versteeg; Mariska M. G. Leeflang (Journal of Tropical Medicine)
Identification of post-kala-azar dermal leishmaniasis (PKDL) is important due to the long and toxic treatment and the fact that PKDL patients may serve as a reservoir for visceral leishmaniasis (VL). We summarized the published literature about the accuracy of diagnostic tests for PKDL. We searched Medline for eligible studies investigating the diagnostic accuracy of any test for PKDL. Study quality was assessed using QUADAS-2. Data were extracted from 21 articles including 43 separate studies. Twenty-seven studies evaluated serological tests (rK39 dipstick, ELISA, DAT, and leishmanin tests), six studies molecular tests, eight microscopy, and two cultures. Only a few of these studies reported a valid estimate of diagnostic accuracy, as most were case-control designs or used a reference standard with low sensitivity. The included studies were very heterogeneous, for example, due to a large variety of reference standards used. Hence, no summary estimates of sensitivity or specificity could be made. We recommend well-designed diagnostic accuracy trials that evaluate, side-by-side, all currently available diagnostics, including clinical symptoms, serological, antigen, molecular, and parasitological tests and possible use of statistical modelling to evaluate diagnostics when there is no suitable gold standard.